Efficient separation of bagasse lignin by freeze–thaw-assisted p-toluenesulfonic acid pretreatment. (May 2022) - Zeng, Huali; Liu, Baojie; Li, Jiao; Li, Mei; Peng, Meijiao; Qin, Chengrong; Liang, Chen; Huang, Caoxing; Li, Xinping; Yao, Shuangquan
Graphical abstract: Highlights: Lignin was separated by freeze–thaw assisted p -TsOH pretreatment. The separation yield of lignin was 89.76%. The concentration of p -TsOH was reduced to 60%. A green and efficient lignin separation method was obtained. Abstract: Lignin separation is an important procedure that benefits multiple industries and in particular biomass transformation efforts. In this study, bagasse lignin was separated by freeze–thaw-assisted p -toluenesulfonic acid ( p -TsOH) pretreatment. The optimal conditions were freezing temperature −60 °C, freezing time 8.0 h, thawing temperature 15 °C, p -TsOH concentration 60%, pretreatment temperature 70 °C, and time 20 min. Lower acid concentrations and temperatures were used compared with traditional p -TsOH pretreatment. The efficiency and selectivity of lignin separation were improved. It was attributed to freeze-thawing, which provided a more efficient physical channel for the effective penetration of p -TsOH. The separation, extraction and purity of lignin were improved to 89.76%, 78.22% and 77.89%, respectively. High separation, high extraction, high purity and large molecular weight lignin samples were obtained. In addition, the recovery and reuse of p -TsOH was enhanced. This provided a new method for the efficient and clean separation of lignin.